A Study on Awareness Level of Services Offered by Depository Participants with Special Reference to Pollachi Taluk, Tamil Nadu - R., Sharmila (Indian Journal of Finance, 2010)
A major reform of the Indian stock markets has been the introduction of depository system and scripless trading mechanism since 1996. The long prevailing scrip based system of securities transaction involves enormous paper work involving certificates and transfer deeds. Every securities transaction, for example in the physical scrip based system is required to be accomplished by physical movement of securities certificate along with the transfer deeds. The process beginning with the purchase of securities till getting the certificates duly transferred and endorsed in the name of the buyer is indeed quite complex and time consuming and is riddled with a wide variety of problems.